Left ventricular high frame rate echo-particle image velocimetry: feasibility and comparison with conventional echocardiography. (4th February 2022) - Strachinaru, M; Voorneveld, J; Keijzer, LBH; Bowen, DJ; Mutluer, FO; Ten Cate, FJ; De Jong, N; Vos, HJ; Bosch, JG; Van Den Bosch, AE
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Echo-Particle Image Velocimetry (echoPIV) tracks speckle patterns from ultrasound contrast agent (UCA) microbubbles injected intravenously, being less angle-sensitive than colour Doppler. One limitation of conventional echoPIV is the inability to accurately resolve high velocities, because of relatively low frame rates.  In contrast, high frame rate (HFR) echoPIV enables tracking of fast flow in the left ventricle (LV). Purpose: To investigate the feasibility and precision of HFR echoPIV in patients. Methods: 19 heart failure patients were included. UCA was infused with a dedicated pump. HFR contrast images were acquired, in apical long axis view (ALAX, ensuring simultaneous visualization of LV inflow and outflow), using a fully-programmable research ultrasound system, with a phased array probe. In the same session, complete echocardiographic studies were obtained using a clinical ultrasound system, with a matrix array probe, including LV UCA. Non-contrast pulsed-wave (PW) Doppler were also obtained in ALAX (Figure 1) from the mitral valve tips (inflow) and the LV outflow tract (outflow). HFR echoPIV image quality and tracking were assessed offline by two independent observers. The peak velocity of the inflow and outflow were determined by the automated tracking algorithm of the HFR echoPIV, and measured by the peak modal velocity of the conventional PW. These velocities were compared using Pearson's correlations and Bland-Altman plots. All patients gave their informed consent. The study was approved by the institutional review board. Results: Conventional echo image quality was good in 12 (63%), medium in 5 (26%) and bad in 2 (11%). EchoPIV tracking was good in 12 (63%), medium in 2 (10%) and bad in 5 (26%). In the 12 patients where echoPIV tracking was good, the direction and velocity of intracavitary vortices could be visualized (Figure 1). The inflow velocity could be determined by echoPIV  in 17/19 (89%), and outflow in 14/19 (74%). EchoPIV tended to underestimate the maximal velocity as determined by PW (Figure 2), with a bias of 0.19 m/s (inflow) and 0.28 m/s (outflow). This negative bias is expected as the PW is assessing maximum velocity in the interrogation kernel whereas echoPIV returns the mean velocity. The correlation of the two methods was good for the inflow (R2 = 0.77, p < 0.001) and moderate for the outflow (R2 = 0.54, p < 0.001). This may be explained by the position of the LV outflow tract deeper in the image, leading to increased attenuation, clutter and reduced lateral resolution. Conclusion: HFR echoPIV has comparable feasibility to routine echocardiography, and the ability to correctly estimate intraventricular flow velocity. It can provide in one acquisition all the functional information that can be detected by routine echocardiography, PW and color Doppler, as well as contrast. It succeeds in surpassing the shortcomings of Doppler (angle dependency) and classical contrast imaging (low frame rate).